Bioinformatics findings reveal the pharmacological properties of ferulic acid treating traumatic brain injury via targeting of ferroptosis - Qinghua Dong; Shenglin Yang; Huafeng Liao; Qi He; Junxin Xiao (International Journal of Food Properties, 2023)
Ferroptosis refers to a lytic cell death avenue that may be related to the development of neuropathological disorders. Traumatic brain injury (TBI) is the brain impairments and ferroptosis is found with the pathological role in TBI development. Our previous findings showed that ferulic acid exerts pharmacological benefited against TBI. However, the therapeutic efficacy and mechanism targeting of ferroptosis in ferulic acid against TBI is still unclear. In current report, an integrated approach by using network pharmacology and molecular docking analyses was subjected to identify the ferulic acid-anti-TBI mechanisms and targets associated with ferroptosis. The network pharmacology analysis had screened 184 ferulic acid-related targets, 1834 TBI-associated targets and 616 ferroptosis-linked targets, characterized with 14 overlapping genes among ferulic acid, TBI, and ferroptosis. All core targets in ferulic acid treating TBI via regulation of ferroptosis were identified through parametric determination, including PTGS2, TLR4, RELA, GSK3B, NFE2L2, EGFR, and MIF. Following with enrichment analysis, anti-TBI functions of ferulic acid against TBI targeting ferroptosis were revealed in multiple biological processes, including regulation of polymerase activities, transcription factor functions, ubiquitin protease binding capabilities. Pharmacological mechanisms were detailed in signaling pathways mainly involved in neuroprotection, microenvironmental restoration and neural regeneration were the key functional characteristics. Further in silico validation exhibited that PTGS2 was a potential pharmacological target associated with ferroptosis in ferulic acid against TBI owing to the potent binding energy. Collectively, current bioinformatics data provide a new preclinical insight of the pharmacological function and mechanism targeting of ferroptosis in ferulic acid treating TBI. Compared to other correlative researches, this study may effectively exhibit the preclinical perspective in new drug research and development on ferulic acid against TBI through revealing multiple targets and pathways.